The Sharing of Reference Strategies across Two Languages: The Production and Comprehension of Referring Expressions by Greek-Italian Bilingual Children - Maria Andreou; Jacopo Torregrossa; Christiane Maria Bongartz (Discours)
Several studies have observed that bilinguals tend to use and accept overspecified, redundant referring expressions in one of their two languages. This tendency has been mainly analysed as an effect of cross-linguistic influence (for instance, from a non-null-subject language to a null-subject one) or quantity and quality of language exposure. We aim to show that, beyond cross-linguistic and language-exposure effects, the use and acceptability of overspecified forms is the outcome of individual patterns of reference management, which are shared across the two languages. We tested 31 Greek-Italian bilingual children by using a narrative task (assessing the use of referring expressions in discourse) and a timed judgement task (related to the interpretation of referring expressions). The results show that reference strategies can be shared between the two languages and, in the bilingual group at stake in this study, this sharing is not modulated by language dominance or proficiency. The study introduces individual variation as one of the factors to consider when dealing with bilingual reference acquisition.